The inner circumstellar dust of the red supergiant Antares as seen with VLT/SPHERE/ZIMPOL. Issue 1 (9th January 2021) - Cannon, E; Montargès, M; de Koter, A; Decin, L; Min, M; Lagadec, E; Kervella, P; Sundqvist, J O; Sana, H
ABSTRACT: The processes by which red supergiants lose mass are not fully understood thus-far and their mass-loss rates lack theoretical constraints. The ambient surroundings of the nearby M0.5 Iab star Antares offer an ideal environment to obtain detailed empirical information on the outflow properties at its onset, and hence indirectly, on the mode(s) of mass-loss. We present and analyse optical VLT/SPHERE/ZIMPOL polarimetric imaging with angular resolution down to 23 milliarcsec, sufficient to spatially resolve both the stellar disc and its direct surroundings. We detect a conspicuous feature in polarized intensity that we identify as a clump containing dust, which we characterize through 3D radiative transfer modelling. The clump is positioned behind the plane of the sky, therefore has been released from the backside of the star, and its inner edge is only 0.3 stellar radii above the surface. The current dust mass in the clump is 1.3^+0.2_-1.0 × 10^-8 M_, though its proximity to the star implies that dust nucleation is probably still ongoing. The ejection of clumps of gas and dust makes a non-negligible contribution to the total mass lost from the star that could possibly be linked to localized surface activity such as convective motions or non-radial pulsations.